Challenges Faced by Secondary English Language Teachers in Integrating ICT in the Classroom - Pant, Chandani (Journal of Research in Education, 2025)
This article explores the challenges faced by secondary level English language teachers in integrating Information and Communication Technology (ICT) while applying in teaching learning activities in the context of community schools of Kanchanpur district, Nepal. The study was based on mixed method design and data was collected from forty English language teachers teaching from secondary level schools of kanchanpur district purposively and data was collected via questionnaire, interviews and classroom observation. Major problems of teaching learning activities were identified via qualitative and quantitative analysis. The findings show that teachers faced pedagogical and administrative challenges higher than the technical ones. Lack of ICT training limited digital competences, low confidence and motivation with extended class size were taken as major barriers. The major administrative obstacles of ICT implementation are high ICT costs, weak policies, poor monitoring and inadequate planning. Along with this, poor internet connectivity and insufficient infrastructure are some major technical problems. The study concludes that effective ICT integration requires teacher training, supportive policies, institutional backing, and improved facilities. Empowering teachers with ICT skills and confidence can transform traditional classrooms into interactive, learner centered spaces, enhancing the quality and relevance of English language education in Nepal.